Characteristic Overview of HIV Patients Receiving Antiretroviral Therapy - Sari, Putri Irwanti; Sukartini, Tintin; Misutarno, Misutarno (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the characteristics of patients with HIV who are undergoing antiretroviral therapy. The study is a quantitative descriptive study carried out in a community health center in Surabaya, East Java province, in February 2020. The population was HIV patients who had received antiretroviral therapy for more than one month. A sample of 35 respondents was recruited using purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability. Data were analyzed descriptively. The frequency distribution of 35 respondents was obtained, with respondents aged 26-35 years at 31.4%, male sex at 48.6%, married at 45.7%, high school education at 31.4%, employment at 65.7%, income less than 500,000 per month at 62.9%, ARV consumption for more than one year at 80% and 60% receiving a fixed-dose combination therapy, 77.1% having a good knowledge level and 71.4% showing good adherence and 57.1% demonstrating fewer methods in providing health education. Characteristics of HIV patients receiving antiretroviral therapy generally include low levels of education and income, but the level of knowledge about HIV disease and respondent adherence to ARVs was good. Low income does not reduce the patient's desire to continue treatment. Support from health workers in providing health education with appropriate methods is expected to increase patient knowledge so that they can commit to adherence with ARV medications.